Pengaruh Label Halal, Kualitas Layanan, dan Lokasi Pelanggan Muslim dengan Minat Beli sebagai Variabel Intervening di Industri Makanan UMKM Kota Ambon Provinsi Maluku - Camelia, Milly; Ekawati, Christina (Sosio e-Kons, 2024)
This thesis, titled "The Influence of Halal Label, Service Quality, and Location on Muslim Customer Loyalty with Purchase Intention as an Intervening Variable in the Food Industry of MSMEs in Ambon City, Maluku Province, Indonesia," is written by Milly Camelia and Christina Ekawati. This research is motivated by the increasing awareness among Muslims about the importance of halal labels. The researcher also observed the increasing growth of food MSMEs in Ambon City following the COVID-19 pandemic, which sparked an interest in investigating the influence of halal labels, service loyalty, and location on customer loyalty, with purchase intention as an intervening variable in food MSMEs in Ambon City. Based on the findings of this research, the researcher concluded that: The halal label variable does not significantly influence the intervening variable of purchase intention, The service quality variable significantly influences the intervening variable of purchase intention, The location variable significantly influences the intervening variable of purchase intention, The halal label variable does not significantly influence the customer loyalty variable, The service quality variable significantly influences the customer loyalty variable, The location variable does not significantly influences the customer loyalty variable, The purchase intention intervening variable significantly influences customer loyalty, and The mediation test results indicate that the purchase intention variable acts as a mediator in the relationship between halal labels, service quality, location, and customer loyalty, though its mediating effect is relatively weak.